Komizm współczesnych filmów rosyjskich na warsztacie tłumacza - Mocarz-Kleindienst, Maria (Studia Rossica Posnaniensia, 2017)
The paper concerns linguistic humour as an aesthetic-cultural category which is at the core of comedy. Linguistic material from contemporary Russian movies and their translations into Polish is analysed. The basic linguistic components creating linguistic humour include neologisms, linguistic games, modifications of phraseological units and intertextual references. The aforementioned components cause many problems in movie translations into a foreign language. The paper attempts to provide an overview of ways of translating.